An Examination of the Market Reactions Associated with SFAS No.8 and SFAS No. 52. - Ziebart, David A.; Kim, David H. (The Accounting Review, 1987)
Abstract ABSTRACT: Previous market-based research has generally failed to detect significantly negative market price reaction to the issuance of SFAS No. 8. Using standardized abnormal returns, this study re-examines the issue. Reaction to events culminating in the issuance of SFAS No. 52 is also studied. Finally, since the accounting method used prior to SFAS No. 8 may be related to the costs imposed by SFAS No. 8, the method is determined and its effect on the observed market reactions is investigated. Our results indicate an overall negative reaction to SFAS No. 8, with a positive reaction to SFAS No. 52. In addition, the pre-SFAS No. 8 method of accounting for foreign currency translation is found to be related to the market reactions to SFAS No. 8 and SFAS No. 52 in mixed and unpredictable ways.